Looking for Felix (big book) - Libby, Hathorn; Culic, Ned (Nelson Australia South Melbourne, 1994)
"Looking for Felix" is a heartwarming story that follows the journey of a young boy named Felix, who embarks on an adventure to find his lost friend. Throughout the narrative, Felix encounters various characters and learns valuable lessons about friendship, perseverance, and the importance of being true to oneself. The story is filled with vibrant illustrations and engaging dialogue, making it appealing to children. As Felix navigates his quest, he discovers that the bonds of friendship can be found in unexpected places, and the journey itself is as significant as the destination. This tale encourages readers to cherish their relationships and embrace the spirit of adventure.